DNA BARCODING IN THE VALIDATION OF SCAD SPECIES IDENTIFICATION (GENUS: DECAPTERUS) IN AMBON - Limmon, Gino Valentino; Purnama, Ray; Mamesah, Julieta A.B.; Manuputty, Gratia D.; Rahman, Rahman (Malaysian Journal of Science, 2024)
Limitations on the morphology-based identification system and the decreasing number of taxonomists have become a problem that requires a molecular approach toward the recognition and identification of species. DNA barcoding has been considered an efficient solution to solve a few of taxonomy’s problems. This research intended to identify several scads species which have been found in the waters surrounding Ambon morphologically and molecularly through DNA barcoding. Fish samples were collected from January to June 2018 at the Mardika fish market Ambon, and then brought to the Laboratory of the Maritime and Marine Science Centre of Excellence Pattimura University for further analysis. Based on morphological identification, six species of scad were discovered, being Decapterus macarellus, D. macarellus (suspected), D. macrosoma, D. macrosoma (suspected), D. russelli (suspected)and D. kurroides. Using DNA barcoding, only four species of scad were found, being D. macarellus, D. macrosoma, D. russelli and D. kurroides with identification percentage ranging from 99-100%. After validation, the species of scad which can be found in Ambon’s waters are D. macarellus, D. macrosoma, D. russelli and D. kurroides. DNA barcoding is a complementary alternative that can reinforce morphology-based identification quickly and accurately.